Can Nonhuman Substrates Dream of Nirvana? Recuperating Subjectivity through Posthuman Spirituality in "Readymade Bodhisattva". Issue 3 (2nd July 2016) - Shin, Haerin
ABSTRACT: Can an inorganic substrate such as an artificially intelligent android achieve Nirvana? Born free of the mortal coil and its toils, what is there for such an entity to awaken from, and to what end? Pak Sŏng-hwan's "Readymade Bodhisattva" (2004) interrogates this question and destabilizes the last bastion of existential aura our kind still holds dear to heart: spirituality. Reading the enlightened robot as an inverted image of the human subject, this essay explores a way out of anthropocentric ontology. I claim that the interactions between various parties of disparate ontological and social strata in the story show that the uncanny alterity of our own simulations is none other than our mirror images and suggest that what we deem to be the essence of our being may in fact be irreconcilably alien to who we are. Enlightenment, in this light, is the self-contradictory knowledge that admits to its own impossibility.